Perspectives on shared reading among a sample of Latino parents. (19th December 2018) - Jimenez, Manuel E.; Hudson, Shawna V.; Lima, Daniel; Mendelsohn, Alan L.; Pellerano, Maria; Crabtree, Benjamin F.
Abstract: Background: Paediatric professionals promote shared reading to facilitate school readiness, yet relatively few studies examine how parents from underserved communities consider this issue in their daily lives. We sought to understand shared reading within the broader context of parenting among Latino parents. Methods: We conducted in‐depth interviews, purposively sampling Spanish‐speaking, Latina mothers of children aged ≤3 years from an urban Federally Qualified Health Center. Interviews were recorded, transcribed, and analysed iteratively. We allowed themes to emerge from data rather than impose an a priori framework. We sought disconfirming evidence within interviews and collected additional data to ensure no new themes were identified (saturation). Results: We achieved saturation after 12 interviews. The median child age was 1.4 years. We identified four major themes: (a) All participants reported engaging in literacy promoting activities such as conversations, storytelling, play, and singing even if they did not read to their children daily. (b) Parents' attitudes regarding early learning and development influenced the extent to which parents engaged in shared reading with their child. (c) Participants described feelings that they ought to read daily with their children but were not and cited a variety of barriers. (d) Parents who engaged in frequent shared reading described it as a joyful and relaxed experience; parents who did not engage in shared reading described reading as instructing children or engaging in drills (e.g., teaching letters). Conclusion: Urban, Latina mothers who did not read regularly with their children nonetheless recognized its importance suggesting that existing programmes have raised awareness even among underserved families. Refinement of messaging may be needed to move past raising awareness to facilitating shared reading for some parents.